Arm Length and Height Relationship in Young Indian Adults: A Correlation and Regression Analysis - Aparna Milind Joshi; Shweta Shankarrao Thorat (Advances in Human Biology)
Introduction: Anthropometric studies on body proportions such as arm length (AL) and height (Ht) are essential for understanding physical growth patterns and health indicators, particularly amongst young adults. However, limited research exists on this relationship in the Indian population. Materials and Methods: This study examined the correlation and regression between AL and Ht in 500 healthy Indian adults aged 18–23 years. Standard anthropometric tools were used to measure AL and Ht, and statistical analyses were conducted to determine the relationship between these variables. Results: The results showed varying degrees of correlation between AL and Ht across different age groups and genders. Males generally exhibited higher AL to Ht ratios compared to females, with significant gender differences observed in younger age groups. Conclusion: These findings contribute to our understanding of human growth patterns amongst young Indian adults and have important implications for clinical assessments and anthropological research. Further, longitudinal studies are recommended to better understand the dynamics of growth and body proportions over time in this population.